The Effect of Fun Thinker’s Book Media on the Mathematical Logic Intelligence of 5 - 6-Year-Old Children - Fakhita Indira Haris; Muhammad Yusri Bachtiar; Muhammad Akil Musi (Universitas Negeri Makassar, 2023)
This study aims to determine the effect of fun thinker's book media on the mathematical logic intelligence of children aged 5-6 years at Nurul Taqwa Kindergarten. The research approach used is quantitative with the type of quasi-experimental design. The research design used is A non-equivalent control group design. The population of this study is children aged 5-6 years of Nurul Taqwa Pattunggalengang Kindergarten, Gowa Regency, with 30 children. The sampling technique used was purposive sampling, so the subjects in this study were 20 children aged 5-6 years. The data collection techniques used in this study were observation, tests, and documentation. The method used is descriptive and nonparametric statistical analysis using the Wilcoxon test. The results of hypothesis testing using the SPSS application show that the data is 2.271 and the sig value. (2- tailed) of 0.023 <0.05, then H1 is accepted and H0 is rejected. The results showed an effect of fun Thinkers book media on the mathematical logic intelligence of children aged 5-6 years at Nurul Taqwa Pattunggalengang Kindergarten, Gowa Regency.